Generic classification of the family pipunculidae (Diptera): A cladistic analysis - Rafael, José Albertino; Meyer, M. de; Meyer, Marc de (Journal of Natural History, 1992)
Classification of the higher taxa of the Pipunculidae is analysed by cladistic techniques. Twenty-five taxa are studied, and 117 character states are examined for these taxa. Based on the cladistic analysis a classification is proposed, recognizing three subfamilies: Chalarinae, Nephrocerinae, and Pipunculinae. The subfamily Pipunculinae is separated into five tribes: Pipunculini, Cephalopsini trib. nov; Microcephalopsini trib. nov., Eudorylini trib. nov., and Tomosvaryellini. Mono- phyletic genus groups within these tribes are recognized. The position of Claraeo- sphaera is unclear. Twenty-three taxa of generic status are recognized, and Wittella is considered synonymous with Cephalops. The genus Collinias is revalidated. Claraeomorpha is retained as a subgenus of Dorylomorpha. A presumed phylogenetic history of the taxa and evolutionary transformation series for certain characters are extrapolated from the analysis. © 1992 Taylor & Francis Ltd.